The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.20944/preprints202002.0082.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Investigating the Gut Microbiota Composition of Individuals with Attention-Deficit/Hyperactivity Disorder and Association with Symptoms

Abstract: Attention-deficit/hyperactivity disorder (ADHD) is a common neurodevelopmental disorder. Given the growing evidence of gut microbiota being involved in psychiatric (including neurodevelopmental) disorders, we aimed to identify differences in gut microbiota composition between participants with ADHD and controls and to investigate the role of the microbiota in inattention and hyperactivity/impulsivity. Fecal samples were collected from 107 participants (NADHD=42; Ncontrols=50; NsubthreholdADHD=15; range age: 13… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(57 citation statements)
references
References 38 publications
(48 reference statements)
4
53
0
Order By: Relevance
“…The metagenomic data here may not directly compare with those results from 16S rRNA sequencing analysis [18][19][20][21][22]. Nevertheless, our findings demonstrated gut dysbiosis in patients with ADHD compared with HCs, which was consistent with previous studies.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…The metagenomic data here may not directly compare with those results from 16S rRNA sequencing analysis [18][19][20][21][22]. Nevertheless, our findings demonstrated gut dysbiosis in patients with ADHD compared with HCs, which was consistent with previous studies.…”
Section: Discussionsupporting
confidence: 64%
“…Notably, the reported distinct bacterial taxa between ADHD patients and HCs were highly inconsistent in previous studies [18][19][20][21][22][23]. The disturbed bacterial taxa in one cohort may never be replicated or may be opposite in abundance in another cohort.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Recently, there are some efforts to control neurological disorders by applying the gut-brain axis theory, a bidirectional communication between the brain and gastrointestinal tract [ 50 , 51 ]. In cases of ADHD, there is evidence demonstrating that gut microbiota affects brain neurodevelopment [ 52 , 53 , 54 , 55 ]. For instance, Szopinska-Tokov et al suggested that inattentive behavior that appeared in ADHD patients is associated with a specific bacterium [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sequencing was performed on the Illumina HiSeq PE300 platform by GATC Biotech AG (Konstanz, Germany). The sequences were processed using NG-Tax (57) analysis pipeline as described previously (58). This resulted in an Operational Taxonomical Unit (OTU) table containing 844 OTUs.…”
Section: Gut Microbiome Analysismentioning
confidence: 99%